« Entrer dans l’immobilité » : les défunts en position assise du second âge du Fer - Valérie Delattre; Laure Pecqueur (Gallia)
The discovery of buried deceased in an atypical position is a standard feature in funerary archaeology and can refer to a kind of banishment, relegation, symbolic punishment. The few Latenian individuals found in a sitting position are constantly of concern to the protohistorians and now put forward a synthetic reflection focusing on a new grid of interpretation that does not any more necessarily stigmatize funerary and/or cult discrepancies, which present the human body. This position seems to transcend the community liturgies and suggests that these selected bodies found on the margin of cemeteries were isolated on purpose from the common mortals: chosen and laid out for the eternity, they now on seem to approach the divine and its expression modalities.